CVD growth of high-quality and large-area continuous h-BN thin films directly on stainless-steel as protective coatings. (December 2021) - Jia, S.; Chen, W.; Zhang, J.; Lin, C.-Y.; Guo, H.; Lu, G.; Li, K.; Zhai, T.; Ai, Q.; Lou, J.
Abstract: Corrosion has been one of the most challenging long-term problems for many industry sectors. It accounts for more than half of the industrial failures and costs tens of billion dollars every year. Hexagonal boron nitride ( h -BN), a chemically inert layered two-dimensional electrical insulator, which is stable at high temperature under an ambient environment, has been considered as a promising candidate for ultrathin protective coatings especially for harsh environments. In this work, we develop an efficient chemical vapor deposition (CVD) method to directly grow high quality, uniform, and large-area continuous h -BN thin films on industry-relevant stainless-steel substrate. During growth, the h -BN crystalline triangles merge together to form a large-area, voids-free, and continuous thin film on both flat and curved surfaces of stainless-steel substrates. The as-grown h -BN thin films could protect the stainless-steel substrates from oxidization under ambient condition at 800 °C and from corrosion in an extremely corrosive solution at both room and elevated temperatures. Graphical abstract: Continuous h -BN films directly grown on stainless-steel as protective coatings. Image 1 Highlights: ● High-quality, uniform, and large-area continuous h -BN films were directly grown on industry relevant stainless-steel substrate. ● The as-grown h -BN thin films could protect stainless-steel substrates from oxidization under ambient condition at 800 °C. ● The continuous h -BN films also could protect stainless-steel substrates from corrosion in an extremely corrosive solution at both room and elevated temperature.